Long-Range Monitoring System with PDMS Material - Norsaidah Muhamad Nadzir; M. K. A. Rahim; F. Zubir; H. A. Majid (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper describes the development of a long range monitoring system that integrates Cottonwood: UHF Long Distance RFID reader module with Raspberry Pi 3. When a UHF RFID tag is within the UHF RFID reader antenna’s range, the unique ID of the tag will be transferred to the Raspberry Pi 3 to be processed. Then, the data will be sent over to the database wirelessly to be managed, stored, and displayed. The paper also describes the measurement done to determine the most suitable thickness of PDMS material so that it could be incorporated as a wearable transponder. After the result is calculated and tabulated, it can be concluded that the most suitable thickness of PDMS material for the transponder is 8 mm.